2004
DOI: 10.1002/pse.173
|View full text |Cite
|
Sign up to set email alerts
|

Laminated timber frames with composite fibre‐reinforced connections

Abstract: Laminated timber frames behave well under dynamic earthquake loads, but the beam-tocolumn connections may be susceptible to a brittle-type failure, due to tensile stresses across wood fibres. Fibre-based materials such as nonwoven glass-fibre fabric are effective in mitigating the tensile failures and increasing the ductility of the connections. While global performance of such connections and frames shows satisfactory results, some fundamental questions associated with the performance of the composite-wood sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Existing studies have reported the development of various methods and techniques to improve the performance of dowel-type timber joints. In order to increase the local bearing capacity of the timber, materials are applied on the surface of the timber member, such as bonded steel plates (Leijten, 1988), punched nail plates (Blaß et al, 2000; Blaß and Schädle, 2011), densified veneer wood (DVW; Leijten, 1991, 1999; Rodd and Leijten, 2003) and glass-fibre-reinforced polymer (GFRP) materials (Chen, 1999; Haller et al, 2006; Haller and Wehsener, 1999; Kasal et al, 2002, 2004a, 2004b). Other strengthening approaches include the insertion of lag screws laterally into the timber members in order to reduce the risk of timber splitting and to carry part of the bolt bearing load (Blaß and Schädle, 2011; Lam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have reported the development of various methods and techniques to improve the performance of dowel-type timber joints. In order to increase the local bearing capacity of the timber, materials are applied on the surface of the timber member, such as bonded steel plates (Leijten, 1988), punched nail plates (Blaß et al, 2000; Blaß and Schädle, 2011), densified veneer wood (DVW; Leijten, 1991, 1999; Rodd and Leijten, 2003) and glass-fibre-reinforced polymer (GFRP) materials (Chen, 1999; Haller et al, 2006; Haller and Wehsener, 1999; Kasal et al, 2002, 2004a, 2004b). Other strengthening approaches include the insertion of lag screws laterally into the timber members in order to reduce the risk of timber splitting and to carry part of the bolt bearing load (Blaß and Schädle, 2011; Lam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bouchair et al (2007) studied the property of plywood as a reinforcing material. The strength and ductility of connections can also be improved by reinforcing the surface of timber members with fiber fabrics, such as textile, glass fiber, and carbon fiber (Haller and Chen, 1999;Haller et al, 1996Haller et al, , 2006Kasal et al, 2004). Steel materials are also suitable as reinforcing materials.…”
Section: Current Improvement Methodsmentioning
confidence: 99%
“…In the case of timber structures, textiles can offer certain structural benefits especially in the form of reinforced joints, see Figure 3c or Figure 3d and [48][49][50]. Apart from the multitude of advantages that can derive from the use of textiles in timber engineering, however, major restrictions and limits could derive from the different thermal performance of the involved materials.…”
Section: Textiles and Fabrics With Traditional Buildings Materialsmentioning
confidence: 99%